Fetal growth, stillbirth, infant mortality and other birth outcomes near UK municipal waste incinerators; retrospective population based cohort and case-control study. (January 2019) - Ghosh, Rebecca E.; Freni-Sterrantino, Anna; Douglas, Philippa; Parkes, Brandon; Fecht, Daniela; de Hoogh, Kees; Fuller, Gary; Gulliver, John; Font, Anna; Smith, Rachel B.; Blangiardo, Marta; Elliott, Paul; et al.
Abstract: Background: Some studies have reported associations between municipal waste incinerator (MWI) exposures and adverse birth outcomes but there are few studies of modern MWIs operating to current European Union (EU) Industrial Emissions Directive standards. Methods: Associations between modelled ground-level particulate matter ≤10 μm in diameter (PM10 ) from MWI emissions (as a proxy for MWI emissions) within 10 km of each MWI, and selected birth and infant mortality outcomes were examined for all 22 MWIs operating in Great Britain 2003–10. We also investigated associations with proximity of residence to a MWI. Outcomes used were term birth weight, small for gestational age (SGA) at term, stillbirth, neonatal, post-neonatal and infant mortality, multiple births, sex ratio and preterm delivery sourced from national registration data from the Office for National Statistics. Analyses were adjusted for relevant confounders including year of birth, sex, season of birth, maternal age, deprivation, ethnicity and area characteristics and random effect terms were included in the models to allow for differences in baseline rates between areas and in incinerator feedstock. Results: Analyses included 1, 025, 064 births and 18, 694 infant deaths. There was no excess risk in relation to any of the outcomes investigated during pregnancy or early life of either mean modelled MWI PM10 or proximity to an MWI. Conclusions: We found no evidence that exposure to PM10 from, or living near to, an MWI operating to current EU standards was associated with harm for any of the outcomes investigated. Results should be generalisable to other MWIs operating to similar standards. Highlights: One of the largest studies to date on health risks of municipal waste incineration Investigated all 22 British municipal waste incinerators (MWIs) operating 2003–10 Used both modelled emissions concentrations and proximity to estimate MWI exposures Examined birth weight, multiple births, sex ratio, prematurity and mortality outcomes Found no associations between MWI proximity or emissions and infant health outcomes